Optoelectronic Neural Networks: An Atomically Thin Optoelectronic Machine Vision Processor (Adv. Mater. 36/2020). Issue 36 (8th September 2020) - Jang, Houk; Liu, Chengye; Hinton, Henry; Lee, Min‐Hyun; Kim, Haeryong; Seol, Minsu; Shin, Hyeon‐Jin; Park, Seongjun; Ham, Donhee
Abstract : In article number 2002431, Seongjun Park, Donhee Ham, and co‐workers describe pioneering work on an optoelectronic neural network built out of 2D MoS2 . They highlight its use in a machine vision processor, which mimics two core functions of human vision to recognize optical images of hand‐written numbers.